SUCCESS ANALYSIS OF KITABISA MOBILE APPLICATION INFORMATION SYSTEM BY USING DELONE AND MCLEAN MODELS - Aditya, Hafiz Noval Hasany; Nurmalasari, Nurmalasari; Hendri, Hendri (Jurnal Pilar Nusa Mandiri, 2020)
KitaBisa, the public can raise funds for a variety of things they do or donate for things they want to help. Starting from the desire to create a social movement, in 2013 Alfatih Timur (Timmy) made KitaBisa a forum for anyone who wanted to realize his social project. Measuring the success of the KitaC mobile application can use the DeLone and McLean model, it is known that variables that have a significant relationship include Service Quality against User Satisfaction with a t-statistic value of 2.893, System Quality for Users (Use) with a t-statistic value of 10,204, and User Satisfaction of the Net Benefit with a t-statistic value of 3,680. In accordance with the hypothesis testing that user satisfaction with the KitaBisa mobile application as a forum to donate online has been proven by influencing User Satisfaction with the Net Benefit as a whole or it means the user has felt the benefits of the KitaBisa mobile application.